Robot service failure and recovery: Literature review and future directions - Liu, Dewen; Li, Changfei; Zhang, Jieqiong; Huang, Weidong (International journal of advanced robotic systems, 2023)
Robot service failure and subsequent user behavioral responses have emerged as a prominent scientific issue, warranting attention from multiple disciplines. A review of existing literature is crucial to synthesizing and comprehensively evaluating these studies. To this end, the present study undertook a structured systematic literature review to assess the relevant research on the concepts, dimensions, user response (including cognitional and behavioral), and recovery strategies related to service robot failure. Prior studies have largely followed interpersonal service interaction concepts and have identified several major consequences of service robot failure, including emotional and cognitive responses, negative attitudes, attributions of failure, and related behavioral and action-based responses. Notably, recovery strategies for robot service failure can be categorized into two main types: robot-initiated strategy and human intervention strategy. Further research on robot service failure is recommended in five key areas, including exploring the uniqueness of robot service failure, psychologically investigating user responses to robot failure, identifying novel remedy strategies for robot service failures, evolving the concepts of robot service failure and its remedies, and employing mixed-method and complementary research approaches.